Feasibility study highlighting the benefits of solar power over grid power for classroom loads - Reza, Sharzana; Patwary, Shadman Sakib; Ahmed, Rashik (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.